Calculus/Integration techniques/Trigonometric Substitution

Integral of sqrt(x+1)/x (substitution + partial fraction decomposition)
Integral of sqrt(x+1)/x (substitution + partial fraction decomposition)

The idea behind the trigonometric substitution is quite simple: to replace expressions involving square roots with expressions that involve standard trigonometric functions, but no square roots. Integrals involving trigonometric functions are often easier to solve than integrals involving square roots.

Let us demonstrate this idea in practice. Consider the expression 1x2{\displaystyle {\sqrt {1-x^{2}}}} . Probably the most basic trigonometric identity is sin2(θ)+cos2(θ)=1{\displaystyle \sin ^{2}(\theta )+\cos ^{2}(\theta )=1} for an arbitrary angle θ{\displaystyle \theta } . If we replace x{\displaystyle x} in this expression by sin(θ){\displaystyle \sin(\theta )} , with the help of this trigonometric identity we see



1 x 2 = 1 sin 2 ( θ ) = cos 2 ( θ ) = cos ( θ ) {\displaystyle {\sqrt {1-x^{2}}}={\sqrt {1-\sin ^{2}(\theta )}}={\sqrt {\cos ^{2}(\theta )}}=\cos(\theta )}

Note that we could write θ=arcsin(x){\displaystyle \theta =\arcsin(x)} since we replaced x2{\displaystyle x^{2}} with sin2(θ){\displaystyle \sin ^{2}(\theta )} .

We would like to mention that technically one should write the absolute value of cos(θ){\displaystyle \cos(\theta )} , in other words |cos(θ)|{\displaystyle {\bigl |}\cos(\theta ){\bigr |}} as our final answer since a2=|a|{\displaystyle {\sqrt {a^{2}}}=|a|} for all possible a{\displaystyle a} . But as long as we are careful about the domain of all possible x{\displaystyle x} and how cos(θ){\displaystyle \cos(\theta )} is used in the final computation, omitting the absolute value signs does not constitute a problem. However, we cannot directly interchange the simple expression cos(θ){\displaystyle \cos(\theta )} with the complicated 1x2{\displaystyle {\sqrt {1-x^{2}}}} wherever it may appear, we must remember when integrating by substitution we need to take the derivative into account. That is we need to remember that dx=cos(θ)dθ{\displaystyle dx=\cos(\theta )d\theta } , and to get a integral that only involves θ{\displaystyle \theta } we need to also replace dx{\displaystyle dx} by something in terms of dθ{\displaystyle d\theta } . Thus, if we see an
integral of the form



1 x 2 d x {\displaystyle \int {\sqrt {1-x^{2}}}dx}

we can rewrite it as



cos ( θ ) cos ( θ ) d θ = cos 2 ( θ ) d θ {\displaystyle \int \cos(\theta )\cos(\theta )d\theta =\int \cos ^{2}(\theta )d\theta }

Notice in the expression on the left that the first cos(θ){\displaystyle \cos(\theta )} comes from replacing the 1x2{\displaystyle {\sqrt {1-x^{2}}}} and the cos(θ)dθ{\displaystyle \cos(\theta )d\theta } comes from substituting for the dx{\displaystyle dx} .

Since cos2(θ)=1+cos(2θ)2{\displaystyle \cos ^{2}(\theta )={\frac {1+\cos(2\theta )}{2}}} our original integral reduces to:

12dθ+12cos(2θ)dθ{\displaystyle {\tfrac {1}{2}}\int d\theta +{\tfrac {1}{2}}\int \cos(2\theta )d\theta } .

These last two integrals are easily handled. For the first integral we get



1 2 d θ = 1 2 θ {\displaystyle {\tfrac {1}{2}}\int d\theta ={\tfrac {1}{2}}\theta }

For the second integral we do a substitution, namely u=2θ,du=2dθ{\displaystyle u=2\theta ,du=2d\theta } to get:



1 2 cos ( 2 θ ) d θ = 1 2 cos ( u ) 1 2 d u = 1 4 sin ( u ) = sin ( 2 θ ) 4 {\displaystyle {\tfrac {1}{2}}\int \cos(2\theta )d\theta ={\tfrac {1}{2}}\int \cos(u){\tfrac {1}{2}}du={\tfrac {1}{4}}\sin(u)={\frac {\sin(2\theta )}{4}}}

Finally we see that:



cos 2 ( θ ) d θ = θ 2 + sin ( 2 θ ) 4 = θ + sin ( θ ) cos ( θ ) 2 {\displaystyle \int \cos ^{2}(\theta )d\theta ={\frac {\theta }{2}}+{\frac {\sin(2\theta )}{4}}={\frac {\theta +\sin(\theta )\cos(\theta )}{2}}}

However, this is in terms of θ{\displaystyle \theta } and not in terms of x{\displaystyle x} , so we must substitute back in order to rewrite the answer in terms of x{\displaystyle x} .

That is we worked out that:



sin ( θ ) = x cos ( θ ) = 1 x 2 θ = arcsin ( x ) {\displaystyle \sin(\theta )=x\qquad \cos(\theta )={\sqrt {1-x^{2}}}\qquad \theta =\arcsin(x)}

So we arrive at our final answer



1 x 2 d x = arcsin ( x ) + x 1 x 2 2 {\displaystyle \int {\sqrt {1-x^{2}}}dx={\frac {\arcsin(x)+x{\sqrt {1-x^{2}}}}{2}}}

As you can see, even for a fairly harmless looking integral this technique can involve quite a lot of calculation. Often it is helpful to see if a simpler method will suffice before turning to trigonometric substitution. On the other hand, frequently in the case of integrands involving square roots, this is the most tractable way to solve the problem. We begin with giving some rules of thumb to help you decide which trigonometric substitutions might be helpful.

If the integrand contains a single factor of one of the forms a2x2 or a2+x2 or x2a2{\displaystyle {\sqrt {a^{2}-x^{2}}}{\mbox{ or }}{\sqrt {a^{2}+x^{2}}}{\mbox{ or }}{\sqrt {x^{2}-a^{2}}}} we can try a trigonometric substitution.

  • If the integrand contains a2x2{\displaystyle {\sqrt {a^{2}-x^{2}}}} let x=asin(θ){\displaystyle x=a\sin(\theta )} and use the identity 1sin2(θ)=cos2(θ){\displaystyle 1-\sin ^{2}(\theta )=\cos ^{2}(\theta )} .
  • If the integrand contains a2+x2{\displaystyle {\sqrt {a^{2}+x^{2}}}} let x=atan(θ){\displaystyle x=a\tan(\theta )} and use the identity 1+tan2(θ)=sec2(θ){\displaystyle 1+\tan ^{2}(\theta )=\sec ^{2}(\theta )} .
  • If the integrand contains x2a2{\displaystyle {\sqrt {x^{2}-a^{2}}}} let x=asec(θ){\displaystyle x=a\sec(\theta )} and use the identity sec2(θ)1=tan2(θ){\displaystyle \sec ^{2}(\theta )-1=\tan ^{2}(\theta )} .
Trigonometric Substitutions
Trigonometric Substitutions
This substitution is easily derived from a triangle, using the Pythagorean Theorem.

If the integrand contains a piece of the form a2x2{\displaystyle {\sqrt {a^{2}-x^{2}}}} we use the substitution



x = a sin ( θ ) d x = a cos ( θ ) d θ {\displaystyle x=a\sin(\theta )\quad dx=a\cos(\theta )d\theta }

This will transform the integrand to a trigonometric function. If the new integrand can’t be integrated on sight then the tan-half-angle substitution described below will generally transform it into a more tractable algebraic integrand.

E.g., if the integrand is 1x2{\displaystyle {\sqrt {1-x^{2}}}} ,



0 1 1 x 2 d x = 0 π 2 1 sin 2 ( θ ) cos ( θ ) d θ = 0 π 2 cos 2 ( θ ) d θ = 1 2 0 π 2 ( 1 + cos ( 2 θ ) ) d θ = π 4 {\displaystyle {\begin{aligned}\int \limits _{0}^{1}{\sqrt {1-x^{2}}}dx&=\int \limits _{0}^{\frac {\pi }{2}}{\sqrt {1-\sin ^{2}(\theta )}}\cos(\theta )d\theta \\&=\int \limits _{0}^{\frac {\pi }{2}}\cos ^{2}(\theta )d\theta \\&={\tfrac {1}{2}}\int \limits _{0}^{\frac {\pi }{2}}{\bigl (}1+\cos(2\theta ){\bigr )}d\theta \\&={\frac {\pi }{4}}\end{aligned}}}

If the integrand is 1+x1x{\displaystyle {\sqrt {\frac {1+x}{1-x}}}} , we can rewrite it as



1 + x 1 x = 1 + x 1 + x 1 + x 1 x = 1 + x 1 x 2 {\displaystyle {\sqrt {\frac {1+x}{1-x}}}={\sqrt {{\frac {1+x}{1+x}}\cdot {\frac {1+x}{1-x}}}}={\frac {1+x}{\sqrt {1-x^{2}}}}}

Then we can make the substitution



0 a 1 + x 1 x 2 d x = 0 α 1 + sin ( θ ) cos ( θ ) cos ( θ ) d θ 0 < a < 1 = 0 α ( 1 + sin ( θ ) ) d θ α = arcsin ( a ) = α + [ cos ( θ ) ] 0 α = α + 1 cos ( α ) = 1 + arcsin ( a ) 1 a 2 {\displaystyle {\begin{aligned}\int \limits _{0}^{a}{\frac {1+x}{\sqrt {1-x^{2}}}}dx&=\int \limits _{0}^{\alpha }{\frac {1+\sin(\theta )}{\cos(\theta )}}\cos(\theta )d\theta &0<a<1\\&=\int \limits _{0}^{\alpha }{\bigl (}1+\sin(\theta ){\bigr )}d\theta &\alpha =\arcsin(a)\\&=\alpha +{\Big [}-\cos(\theta ){\Big ]}_{0}^{\alpha }\\&=\alpha +1-\cos(\alpha )\\&=1+\arcsin(a)-{\sqrt {1-a^{2}}}\end{aligned}}}

This substitution is easily derived from a triangle, using the Pythagorean Theorem.

When the integrand contains a piece of the form
a2+x2{\displaystyle {\sqrt {a^{2}+x^{2}}}}
we use the substitution



x = a tan ( θ ) x 2 + a 2 = a sec ( θ ) d x = a sec 2 ( θ ) d θ {\displaystyle x=a\tan(\theta )\qquad {\sqrt {x^{2}+a^{2}}}=a\sec(\theta )\qquad dx=a\sec ^{2}(\theta )d\theta }

E.g., if the integrand is (x2+a2)32{\displaystyle (x^{2}+a^{2})^{-{\frac {3}{2}}}} then on making this substitution we find



0 z ( x 2 + a 2 ) 3 2 d x = a 2 0 α cos ( θ ) d θ z > 0 = a 2 [ sin ( θ ) ] 0 α α = arctan ( z a ) = a 2 sin ( α ) = a 2 z a 1 + z 2 a 2 = z a 2 a 2 + z 2 {\displaystyle {\begin{aligned}\int \limits _{0}^{z}(x^{2}+a^{2})^{-{\frac {3}{2}}}dx&=a^{-2}\int \limits _{0}^{\alpha }\cos(\theta )d\theta &z>0\\&=a^{-2}{\Big [}\sin(\theta ){\Big ]}_{0}^{\alpha }&\alpha =\arctan \left({\tfrac {z}{a}}\right)\\&=a^{-2}\sin(\alpha )\\&=a^{-2}{\frac {\frac {z}{a}}{\sqrt {1+{\frac {z^{2}}{a^{2}}}}}}\\&={\frac {z}{a^{2}{\sqrt {a^{2}+z^{2}}}}}\end{aligned}}}

If the integral is



I = 0 z x 2 + a 2 z > 0 {\displaystyle I=\int \limits _{0}^{z}{\sqrt {x^{2}+a^{2}}}\qquad z>0}

then on making this substitution we find



I = a 2 0 α sec 3 θ d θ α = tan 1 ( z / a ) = a 2 0 α sec θ d tan θ = a 2 [ sec θ tan θ ] 0 α a 2 0 α sec θ tan 2 θ d θ = a 2 sec α tan α a 2 0 α sec 3 θ d θ + a 2 0 α sec θ d θ = a 2 sec α tan α I + a 2 0 α sec θ d θ {\displaystyle {\begin{matrix}I&=&a^{2}\int _{0}^{\alpha }\sec ^{3}\theta \,d\theta &&&\alpha =\tan ^{-1}(z/a)\\&=&a^{2}\int _{0}^{\alpha }\sec \theta \,d\tan \theta &&&\\&=&a^{2}[\sec \theta \tan \theta ]_{0}^{\alpha }&-&a^{2}\int _{0}^{\alpha }\sec \theta \tan ^{2}\theta \,d\theta &\\&=&a^{2}\sec \alpha \tan \alpha &-&a^{2}\int _{0}^{\alpha }\sec ^{3}\theta \,d\theta &+a^{2}\int _{0}^{\alpha }\sec \theta \,d\theta \\&=&a^{2}\sec \alpha \tan \alpha &-&I&+a^{2}\int _{0}^{\alpha }\sec \theta \,d\theta \\\end{matrix}}}

After integrating by parts, and using trigonometric identities, we’ve ended up with an expression involving the original integral. In cases like this we must now rearrange the equation so that the original integral is on one side only



I {\displaystyle I}



= a 2 2 ( sec ( α ) tan ( α ) + 0 α sec ( θ ) d θ ) {\displaystyle ={\tfrac {a^{2}}{2}}{\Bigg (}\sec(\alpha )\tan(\alpha )+\int \limits _{0}^{\alpha }\sec(\theta )d\theta {\Bigg )}}



= a 2 2 ( sec ( α ) tan ( α ) + [ ln ( sec ( θ ) + tan ( θ ) ) ] 0 α ) {\displaystyle ={\tfrac {a^{2}}{2}}{\Bigg (}\sec(\alpha )\tan(\alpha )+{\bigg [}\ln {\Big (}\sec(\theta )+\tan(\theta ){\Big )}{\bigg ]}_{0}^{\alpha }{\Bigg )}}



= a 2 2 ( sec ( α ) tan ( α ) + a 2 ln ( sec ( α ) + tan ( α ) ) ) {\displaystyle ={\tfrac {a^{2}}{2}}{\bigg (}\sec(\alpha )\tan(\alpha )+a^{2}\ln {\Big (}\sec(\alpha )+\tan(\alpha ){\Big )}{\bigg )}}



= a 2 2 ( z a 2 a 2 + z 2 + ln ( z + a 2 + z 2 a ) ) {\displaystyle ={\tfrac {a^{2}}{2}}{\bigg (}{\tfrac {z}{a^{2}}}{\sqrt {a^{2}+z^{2}}}+\ln \left({\tfrac {z+{\sqrt {a^{2}+z^{2}}}}{a}}\right){\bigg )}}



= 1 2 ( z z 2 + a 2 + a 2 ln ( z + a 2 + z 2 a ) ) {\displaystyle ={\tfrac {1}{2}}{\bigg (}z{\sqrt {z^{2}+a^{2}}}+a^{2}\ln \left({\tfrac {z+{\sqrt {a^{2}+z^{2}}}}{a}}\right){\bigg )}}

As we would expect from the integrand, this is approximately z22{\displaystyle {\frac {z^{2}}{2}}} for large z{\displaystyle z} .

In some cases it is possible to do trigonometric substitution in cases when there is no {\displaystyle {\sqrt {\ \ }}} appearing in the integral.

Example



d x x 2 + 1 {\displaystyle \int {\frac {dx}{x^{2}+1}}}

The denominator of this function is equal to (1+x2)2{\displaystyle {\bigl (}{\sqrt {1+x^{2}}}{\bigr )}^{2}} . This suggests that we try to substitute x=tan(u){\displaystyle x=\tan(u)} and use the identity 1+tan2(u)=sec2(u){\displaystyle 1+\tan ^{2}(u)=\sec ^{2}(u)} . With this substitution, we obtain that dx=sec2(u)du{\displaystyle dx=\sec ^{2}(u)du} and thus



d x x 2 + 1 = sec 2 ( u ) tan 2 ( u ) + 1 d u {\displaystyle \int {\frac {dx}{x^{2}+1}}=\int {\frac {\sec ^{2}(u)}{\tan ^{2}(u)+1}}du}



= sec 2 ( u ) sec 2 ( u ) d u {\displaystyle =\int {\frac {\sec ^{2}(u)}{\sec ^{2}(u)}}du}



= d u {\displaystyle =\int du}



= u + c {\displaystyle =u+c}

Using the initial substitution
u=arctan(x){\displaystyle u=\arctan(x)}
gives



d x x 2 + 1 = arctan ( x ) + C {\displaystyle \int {\frac {dx}{x^{2}+1}}=\arctan(x)+C}

This substitution is easily derived from a triangle, using the Pythagorean Theorem.

If the integrand contains a factor of the form x2a2{\displaystyle \displaystyle {\sqrt {x^{2}-a^{2}}}} we use the substitution



x = a sec ( θ ) d x = a sec ( θ ) tan ( θ ) d θ x 2 a 2 = a tan ( θ ) {\displaystyle x=a\sec(\theta )\quad dx=a\sec(\theta )\tan(\theta )d\theta \quad {\sqrt {x^{2}-a^{2}}}=a\tan(\theta )}

Find 0zx21xdx{\displaystyle \int \limits _{0}^{z}{\frac {\sqrt {x^{2}-1}}{x}}dx} .



0 z x 2 1 x d x {\displaystyle \int \limits _{0}^{z}{\frac {\sqrt {x^{2}-1}}{x}}dx}



= 0 α tan ( θ ) sec ( θ ) sec ( θ ) tan ( θ ) d θ z > 1 {\displaystyle =\int \limits _{0}^{\alpha }{\frac {\tan(\theta )}{\sec(\theta )}}\sec(\theta )\tan(\theta )d\theta \qquad z>1}



= 0 α tan 2 ( θ ) d θ α = arcsec ( z ) {\displaystyle =\int \limits _{0}^{\alpha }\tan ^{2}(\theta )d\theta \qquad \qquad \qquad \qquad \alpha =\operatorname {arcsec}(z)}



= [ tan ( θ ) θ ] 0 α tan ( α ) = sec 2 ( α ) 1 {\displaystyle ={\bigg [}\tan(\theta )-\theta {\bigg ]}_{0}^{\alpha }\qquad \qquad \qquad \tan(\alpha )={\sqrt {\sec ^{2}(\alpha )-1}}}



= tan ( α ) α tan ( α ) = z 2 1 {\displaystyle =\tan(\alpha )-\alpha \qquad \qquad \qquad \qquad \tan(\alpha )={\sqrt {z^{2}-1}}}



= z 2 1 arcsec ( z ) {\displaystyle ={\sqrt {z^{2}-1}}-\operatorname {arcsec}(z)}

Find 1zx21x2dx{\displaystyle \int \limits _{1}^{z}{\frac {\sqrt {x^{2}-1}}{x^{2}}}dx} .



1 z x 2 1 x 2 d x {\displaystyle \int \limits _{1}^{z}{\frac {\sqrt {x^{2}-1}}{x^{2}}}dx}



= 1 α tan ( θ ) sec 2 ( θ ) sec ( θ ) tan ( θ ) d θ z > 1 {\displaystyle =\int \limits _{1}^{\alpha }{\frac {\tan(\theta )}{\sec ^{2}(\theta )}}\sec(\theta )\tan(\theta )d\theta \qquad z>1}



= 0 α sin 2 ( θ ) cos ( θ ) d θ α = arcsec ( z ) {\displaystyle =\int \limits _{0}^{\alpha }{\frac {\sin ^{2}(\theta )}{\cos(\theta )}}d\theta \qquad \qquad \qquad \alpha =\operatorname {arcsec}(z)}

We can now integrate by parts



1 z x 2 1 x 2 d x {\displaystyle \int \limits _{1}^{z}{\frac {\sqrt {x^{2}-1}}{x^{2}}}dx}



= [ tan ( θ ) cos ( θ ) ] 0 α + 0 α sec ( θ ) d θ {\displaystyle =-{\bigg [}\tan(\theta )\cos(\theta ){\bigg ]}_{0}^{\alpha }+\int \limits _{0}^{\alpha }\sec(\theta )d\theta }



= sin ( α ) + [ ln ( sec ( θ ) + tan ( θ ) ) ] 0 α {\displaystyle =-\sin(\alpha )+{\bigg [}\ln {\bigl (}\sec(\theta )+\tan(\theta ){\bigr )}{\bigg ]}_{0}^{\alpha }}



= ln ( sec ( α ) + tan ( α ) ) sin ( α ) {\displaystyle =\ln {\bigl (}\sec(\alpha )+\tan(\alpha ){\bigr )}-\sin(\alpha )}



= ln ( z + z 2 1 ) z 2 1 z {\displaystyle =\ln {\bigl (}z+{\sqrt {z^{2}-1}}{\bigr )}-{\frac {\sqrt {z^{2}-1}}{z}}}

Evaluate the following using an appropriate trigonometric substitution.


Solution

You are watching: Calculus/Integration techniques/Trigonometric Substitution. Info created by THVinhTuy selection and synthesis along with other related topics.

Rate this post

Related Posts